El maltrato educativo y su incidencia en la deserción escolar de los estudiantes de la Unidad Educativa “23 de Junio” Baba. 2022 - Crespo Peñafiel, María Fernanda (2023)
The present research work sought to determine the incidence of educational mistreatment in school dropout. In today's education, school dropout is increasingly recurrent, even more in cities with a high percentage of students in rural or marginal urban areas, who encounter a high degree of difficulties in accessing education. If this stigmatization of students from rural or marginal urban areas is added to the bullying or educational mistreatment suffered by students, this becomes a social problem in the educational field that must be considered. The present investigation dealt with mistreatment among educational peers, which is one of the most common forms of mistreatment in school dropout. This research was conducted at the "23 de Junio" Educational Unit in the city of Baba, province of Los Ríos, Ecuador. A survey was made to the totality of the population affected in the study, dropout students in the school period 2022 - 2023, of the last two years of high school, which was thirty-seven students. Three questions were applied with a qualitative approach, which was analyzed based on the response of all students; and seven questions with a quantitative indicator, which was of a quantitative approach of a descriptive correlational type.